HAKIKAT JIWA DALAM HARMONI AKAL, NAFSU, DAN RUH:KAJIAN PEMIKIRAN IMAM AL-GHAZALI - Afifah Nabil Hasna Aisy; Salsabila Nur Hasan; Lukman Tirjaya Abadi (El-Fikr)
This study explores Imam Al-Ghazali’s thoughts on the essence of the soul and its harmony with intellect, desire (nafs), and spirit (ruh), as elaborated in Iḥyā’ ‘Ulūm ad-Dīn. The focus of this research lies in analyzing the roles of these three elements in shaping human perfection (insan kamil). This study holds academic relevance as it addresses the need for a comprehensive examination of the soul’s concept amidst modernity’s tendency to neglect spirituality. Employing a qualitative method with a hermeneutic approach, this research interprets the textual meanings contextually and philosophically. The findings indicate that Imam Al-Ghazali offers a holistic approach through soul purification (tazkiyatun nafs), involving the stages of takhalli (removing vices), tahalli (adopting virtues), and tajalli (experiencing divine presence). This approach is highly relevant for establishing balance among emotional, intellectual, and spiritual dimensions as a path to human perfection.